Rodovna i sklonidbena dvojnost imenica u hrvatskome jeziku - Bošnjak Botica, Tomislava; Budja, Jurica; Hržica, Gordana (2018)
Novija istraživanja o morfološkom preobilju podastrla su dovoljno podataka koji dovode u pitanje dosad prevladavajuće mišljenje da jezik izbjegava sinonimiju, odnosno da postojanje jednoga oblika sprječava nastajanje drugoga oblika istoga značenja. U ovom se radu ta pojava obrađuje u okviru hrvatske imenične fleksije, u imenica koje pripadaju dvama rodovima i dvjema sklonidbenim vrstama. Istraživanje prati pojavu i zastupljenost deset odabranih imenica kroz dijakronijske i suvremene potvrde.
Recent studies on morphological doublets (overview, Naghzguy-Kohan and Kuteva 2016) have provided many examples that challenge the assumed existence of the blocking effect or synonymy avoidance in language (e.g. Aronoff 1976, Carstairs-McCarthy 2010). Using corpus data, we present this issue in the light of the nominal inflectional morphology of the Croatian language. In principle, the Croatian language displays a clear correspondence between grammatical form and gender. However, some nouns appear with two genders and two inflectional classes. The nouns researched here end in a consonant in the N.sg. and are attested both in the a-declension (masculine gender) and the i-declension (feminine gender). Ten double-gender and double-declension nouns were selected (bol ‘pain’, čar ‘spell, enchantment, charm’, glad ‘hunger, famine’, trulež i gnjilež ‘rot, decay’, živež ‘provisions’, izrast ‘growth’, varoš ‘town’, pelud ‘pollen’, splav ‘raft’). Relevant historical documents from the onset of Croatian literacy were analysed to describe the one-gender stage of the noun (if possible) and to detect the appearance of the second paradigm. Two relevant corpora were used to determine the ratio between two paradigms: CLC, the Croatian Language Corpus (Ćavar and Brozović Rončević 2012) and HrWaC, the Croatian Web Corpus (Ljubešić and Klubička 2014). The study focuses on five questions: 1. Do these nouns appear in two genders in Croatian texts? 2. Will the transition period end in exclusively one declension (and gender)? 3. Is there a constant ratio between the two inflection classes (and genders) through time? 4. How fast is the change, i.e. do rival patterns disappear rapidly? 5. Is this a case of internal or external change? In most current texts, nine out of ten nouns appear in both genders in their respective declensions, but they differ in the ratio between the two patterns.
Bibliografija: str. 85-87.
Sažetak ; Abstract.
Keywords: Hrvatski jezik -- Morfološka sinonimija -- Dvorodne imenice